The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/gps.930080112
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in the nursing home: A selective review of studies related to clinical care

Abstract: SUMMARYExisting research demonstrates that nursing homes are the modern mental institutions for the elderly in the United States, but that training of staff and physicians, processes of care, and the recognition and treatment of mental disorders lag behind the current state of scientific knowledge. The prevalence of diagnosable psychiatric disorders has been estimated to be 80% or higher. The most common of these disorders are the dementias, primarily Alzheimer's or vascular, that can be uncomplicated or compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 97 publications
(49 reference statements)
3
41
0
Order By: Relevance
“…Indeed, there is evidence that Blacks in nursing homes have poorer physical health and worse cognitive functioning than Whites (Belgrave & Bradsher, 1994;Engle & Graney, 1995;Stegbauer et al, 1995). There exists extensive literature concerning both the over-and underuse of various medications in nursing homes (Kim & Rovner, 1995;Rovner et al, 1990Rovner et al, , 1991Rovner & Katz, 1992;Samuels & Katz, 1995). Little is known about medication usage in predominantly Black nursing homes, although possible differences between Blacks and Whites, such as culture, patient symptoms, and type of patient, may result in differences in prescribing habits.…”
Section: Vol 38 No 3 1998 353mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is evidence that Blacks in nursing homes have poorer physical health and worse cognitive functioning than Whites (Belgrave & Bradsher, 1994;Engle & Graney, 1995;Stegbauer et al, 1995). There exists extensive literature concerning both the over-and underuse of various medications in nursing homes (Kim & Rovner, 1995;Rovner et al, 1990Rovner et al, , 1991Rovner & Katz, 1992;Samuels & Katz, 1995). Little is known about medication usage in predominantly Black nursing homes, although possible differences between Blacks and Whites, such as culture, patient symptoms, and type of patient, may result in differences in prescribing habits.…”
Section: Vol 38 No 3 1998 353mentioning
confidence: 99%
“…However, Class and colleagues also found that five of nine Black patients with a primary mood disorder were not receiving antidepressant medication. Clearly, additional studies are needed with large minority samples, particularly for those persons witn a diagnosis of dementia because of the high comorbidity of dementia with depression and other neuropsychiatric disorders (Rovner & Katz, 1992).…”
Section: Vol 38 No 3 1998 353mentioning
confidence: 99%
“…This may have captured some people without a formal mental illness, including those with cognitive impairment attributable to other causes and people with subthreshold depression. However, mild depressive symptoms are often clinically significant, 168,169 and feedback from practitioners suggested the study did accurately identify those older people with mental health problems who commonly present to social services. An unavoidable weakness of the sampling process was that it only captured those older care home entrants known to social or specialist mental health services.…”
Section: Methodological Considerations/lessons For Future Studiesmentioning
confidence: 99%
“…In residents of nursing homes the incidence of mental disorders has been estimated to be 80% or higher [1]. Cognitive impairments, primarily the dementias, are the most prevalent, but major depressive disorders and depressive symptoms have been documented to be 13-48% in both American and European facilities [2,3].…”
Section: Introductionmentioning
confidence: 99%